New approaches in diagnostics of cardiovascular diseases - Yu. A. Dyleva; O. V. Gruzdeva; E. G. Uchasova; A. A. Kuzmina (Лечащий Врач, 2021)
The review is devoted to the description of a number of modern technologies called omixes, including genomics, transcriptome, proteomics, metabolomics, lipidomics and multimarker strategy, whose most important goals is the development of biomarkers for the diagnostics of cardiovascular diseases. The article reflects the achievements of these methods to date and the principles of their application in modern clinical practice for the early diagnostics of diseases, unresolved issues and future prospects.